AB-Initio Investigation Of Structural, Electronic, And Adsorption Properties Of Graphitic Carbon Nitride Sheet With Embedded Transition Metal Mn And Fe Atoms - Abdullahi, Yusuf Zuntu (2018)
At present, research interest in magnetic nanostructures are directed towards the search for suitable substrates for transition metal (TM) atoms embedment. The appropriate substrate is expected to preserve its intrinsic properties and that of bound TM atoms. Graphene and related surfaces with uniformly compacted hexagonal rings have been a frequent choice for trapping TM atoms due to their desirable surface properties. However, reports have shown that the TM atoms diffuse easily on these 2D surfaces as a result of low adsorption energies. To ensure the immobility of the TM atoms on the surface, much efforts have been made to synthesise 2D materials with inherently regular cavities e.g, carbon nitride (CN).